Further phenotypic heterogeneity of CoQ10 deficiency associated with steroid resistant nephrotic syndrome and novel COQ2 and COQ6 variants. Issue 2 (22nd March 2017) - Gigante, M.; Diella, S.; Santangelo, L.; Trevisson, E.; Acosta, M.J.; Amatruda, M.; Finzi, G.; Caridi, G.; Murer, L.; Accetturo, M.; Ranieri, E.; Ghiggeri, G.M.; et al.
Abstract :